The Relation between Workaholism and Organizational Commitment for Supply Chain Success - Hossein Rahimi Koloor; Naser Seifollahi (International Journal of Supply Chain Management, 2018)
Working conditions in todays organizations are such that many people devote a significant part of their life and time to work. One consequence of this situation is the formation of workaholism. Workaholism or addiction to work is to spend considerable time on the job. The current research examines the impacts of workaholism on organizational commitment for supply chain success.An analysis of the data resulting from 340 statistical samples of the managers and personnel in the Supreme Audit Court of Iran indicates a significant and positive correlation between workaholism and organizational commitment for supply chain success by correlation coefficient (0.000) and significance number (0.000). In addition, an analysis of the statistical data shows a positive and significant relationship between the dimensions of workaholism and organizational commitment for supply chain success, indicating the fact that one of the main factors related to organizational commitment is workaholism, and increasing attention should be paid to it in the area of organizational commitment for supply chain success.